2004
DOI: 10.1097/01.brs.0000090823.12652.f9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Osteoinduction by Grafton Demineralized Bone Matrix in Nonhuman Primate Spinal Fusion

Abstract: The rhesus Matrix formulation performed better than the human Flex. Evidence of osteoinduction was seen in all four monkeys that received Matrix, which improved the fusion success of autograft. This alone suggested that it might play a role as a graft enhancer, not merely as a graft extender. Human studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…18,39 Demineralized bone matrix, commercially produced under the name Grafton Allogeneic Bone Matrix (Osteotech, Eatontown, NJ), is combined with glycerol. The osteoinductive nature of Grafton has been shown in animal models, 43,44 and preclinical studies have shown positive performance when used alone and as an extender of autograft. 41,42 Other commercially available demineralized A score of 2 was given to those spines that were considered fused.…”
Section: Discussionmentioning
confidence: 95%
“…18,39 Demineralized bone matrix, commercially produced under the name Grafton Allogeneic Bone Matrix (Osteotech, Eatontown, NJ), is combined with glycerol. The osteoinductive nature of Grafton has been shown in animal models, 43,44 and preclinical studies have shown positive performance when used alone and as an extender of autograft. 41,42 Other commercially available demineralized A score of 2 was given to those spines that were considered fused.…”
Section: Discussionmentioning
confidence: 95%
“…DBM has also been shown in preclinical and clinical studies to be efficacious as an adjuvant to autograft for lumbar fusion as well as a potential bone graft extender. 37,[53][54][55][56] Additionally, the combination of bone marrow aspirates with DBM and allograft chips in a selective retention system has been shown to result in a graft matrix enriched with a 3-to 4-fold increase in osteoprogenitor cells. 39,42,43 It is important to understand in a revision setting how the fusion rates when using bone marrow aspirates with allograft will compare to autogenous bone as well as to the use of off-label rhBMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Louis-Ugbo et al 19 defined graft extenders, enhancers, and substitutes as follows: When added to autogenous bone, graft extenders enable the fusion of more levels or the use of smaller amounts of autogenous bone and should produce a successful fusion equal to that of autogenous bone graft alone. When added to the usual amount or a decreased amount of autogenous bone, graft enhancers produce a higher rate of successful fusions than autogenous bone graft alone.…”
Section: Definitions Of Graft Extenders Enhancers and Substitutesmentioning
confidence: 99%